Knowledge of university students about the use of the female condom (Research, Society and Development, 2023)
The objective of this research was to evaluate the knowledge about the use of the female condom by university students at a public institution, as well as to characterize the sociodemographic and economic variables of the studied population, identifying accessibility and barriers to the use of the female condom. This is a descriptive, cross-sectional and quantitative study to be carried out in a public higher education institution with a sample of 133 academics. It was found that the academics are mostly in the 18-28 age group, corresponding to 90.22% of the sample, 75.2% are single, 53.4% ​​of the fourth year of the course, live with their family, in their own residence, do not work and have an income of one minimum wage. With regard to knowledge, they present inadequate in two courses Administration 73% and Pedagogy 87.5%, adequate in Biology 56.8% and Nursing 73.4%. As for accessibility and barriers, it is noticeable that they are driven by the curiosity of those acquired in basic health units, and the greatest impediment was the difficulty of insertion. As for the orientations, we noticed that the Biology course was the least orientated in relation to the other courses.